Through their eyes: Student perspectives - Alexandra Hartline; Sheri Conklin; Amy Garrett Dikkers (Flexible Learning Association of New Zealand, 2022)
Connecting with students has been shown to increase motivation, satisfaction, and perceived learning while decreasing anxiety. Connecting with students in an online or distance education environment can prove difficult. This study examined perceptions of higher education students who were enrolled in various modalities (e.g., hybrid, online asynchronous, and synchronous) during the COVID-19 pandemic in the United States of America. The study found that a high perception of instructor connectedness in the asynchronous classes resulted in lower anxiety levels for students. Four themes emerged from the results: the importance of instructor empathy; sociability; feedback; and course organisation. These helped students to connect to their instructor-thus reducing anxiety.